ANALISIS RETORIKA HUKUM PADA KONTEN KEBENCIAN DALAM MEDIA SOSIAL TIKTOK: DAMPAK DAN STRATEGI PENANGGULANGANNYA - Habiba Tsalisa Shofiah; Alfianita; Alfi Najua Nabila; Ayu Diana; Thio Zaki Pamungkas; Endang Sholihatin (STKIP Subang, 2024)
This study analyzes hate-related legal rhetoric in TikTok social media, focusing on its impact and countermeasure strategies. This study not only discusses the impact of hateful rhetoric, but also offers countermeasure strategies, making it more comprehensive and providing applicable solutions. Hateful rhetoric on social media has become an increasingly serious problem, and this study makes an important contribution to understanding and addressing the problem. Using a novel and innovative approach, this research examines hateful rhetoric in social media, potentially making a significant contribution to science and public policy related to hateful rhetoric in social media. The objectives of this research are: 1) To identify the most frequent forms of hateful rhetoric in social media in Indonesia, 2) Knowing the impact of hate rhetoric on tolerance, polarization, and fragmentation of society, 3) Knowing a more effective and applicable strategy to counter hateful rhetoric. This research uses a qualitative approach with a critical discourse analysis method to analyze TikTok video content that contains elements of hatred. The results are expected to provide a deeper understanding of the phenomenon of hate rhetoric on social media and offer solutions that can be applied to tackle this problem.